NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI PESTA MATA AIR DAN SUMUR TUA DI DESA BANGUN KABUPATEN BUTON SELATAN - Wa Ode Murnianti Sabowaka; Rusli; Jufri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the Islamic educational values ​​contained in the spring and old well festival tradition in Bangun Village, its internalization process in community life, and its relevance to current social conditions. This study uses a qualitative approach with a Phenomenography type, with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the tradition contains Islamic educational values ​​in the form of faith, worship, morals, and muamalah. The value of faith is reflected in the community's belief that water is a gift from Allah SWT, the value of worship is seen in the implementation of collective prayers as a form of gratitude, the value of morals is seen in the attitude of mutual cooperation and concern for the environment, and the value of muamalah is seen in harmonious social relations between residents. The process of internalization of these values ​​takes place through habits carried out from generation to generation, active community participation, and the example of community leaders. In addition, the Islamic educational values ​​in this tradition are still relevant in today's community life because they are able to strengthen faith, strengthen social relations, and raise awareness in protecting the environment.